2021
DOI: 10.3389/fpsyt.2020.596337
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of Low-Frequency Oscillations in Major Depressive Disorder With Childhood Trauma

Abstract: Major Depressive Disorder (MDD) with childhood trauma is one of the functional subtypes of depression. Frequency-dependent changes in the amplitude of low-frequency fluctuations (ALFF) have been reported in MDD patients. However, there are few studies on ALFF about MDD with childhood trauma. Resting-state functional magnetic resonance imaging was used to measure the ALFF in 69 MDD patients with childhood trauma (28.7 ± 9.6 years) and 30 healthy subjects (28.12 ± 4.41 years). Two frequency bands (slow-5: 0.010–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Therefore, the deviation of non-specific physiological signal components is smaller (Zou et al, 2008 ). A large amount of neuroimaging evidence has demonstrated abnormal brain function and structure in patients with MDD in the resting state (Lai and Wu, 2015 ; Gray et al, 2020 ; Wu et al, 2020 ; Chase et al, 2021 ; Ebneabbasi et al, 2021 ). A study by Wang et al ( 2012 ) involving 18 first-episode, untreated patients with MDD and 18 healthy controls (HCs) found that patients with MDD had significantly higher fALFF values in the right precentral gyrus, right inferior temporal gyrus, bilateral fusiform gyrus, and bilateral anterior and posterior cerebellar lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the deviation of non-specific physiological signal components is smaller (Zou et al, 2008 ). A large amount of neuroimaging evidence has demonstrated abnormal brain function and structure in patients with MDD in the resting state (Lai and Wu, 2015 ; Gray et al, 2020 ; Wu et al, 2020 ; Chase et al, 2021 ; Ebneabbasi et al, 2021 ). A study by Wang et al ( 2012 ) involving 18 first-episode, untreated patients with MDD and 18 healthy controls (HCs) found that patients with MDD had significantly higher fALFF values in the right precentral gyrus, right inferior temporal gyrus, bilateral fusiform gyrus, and bilateral anterior and posterior cerebellar lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent frequency-specific studies demonstrated that functional alterations in Parkinson’s disease were more prominent in slow-4 ( Liao et al, 2021 ), while in Alzheimer’s disease, slow-5 can be more sensitive ( Han et al, 2011 ). However, more studies suggested the two frequency bands offer complementary information ( Wu et al, 2020 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, resting-state functional magnetic resonance imaging (rs-fMRI) has played an important role in studying brain functional activity as a safe, noninvasive technique, which reflects neural activity via blood oxygen level-dependent (BOLD) signals (Mosier et al, 1999 ; Mosier and Bereznaya, 2001 ; Suzuki et al, 2003 ; Zhang et al, 2020 ; Ma et al, 2021 ). Amplitude of low-frequency fluctuations (ALFF) and regional homogeneity (ReHo) are two classic local indices of rs-fMRI, which are widely used due to good stability (Qiu et al, 2019 ; Wu et al, 2020 ). ALFF has been calculated as the mean amplitude of the BOLD signal deviating from baseline over a short period of time, reflecting the strength of the spontaneous neural activity in voxels (Zang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%